Pengaruh Brand Awareness dan Event Marketing terhadap Keputusan Menabung Pada Bank Syariah Indonesia di KCP Medan A.H Nasution - Fathiya Syahidah Nasution; Atika; Fauzi Arif Lubis (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study aims to analyze the influence of brand awareness and event marketing on savings decisions at Bank Syariah Indonesia, specifically at the BSI KCP Medan A.H. Nasution branch. The background of this study is based on the phenomenon of an increasing number of customers despite a previous service system disruption that had the potential to undermine public trust. The research method used is a quantitative approach with data collection techniques via a questionnaire distributed to BSI customers. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression. The results indicate that brand awareness and event marketing have a significant influence, both partially and simultaneously, on savings decisions. This indicates that the stronger the brand awareness and the more effective the event-based marketing activities, the higher the tendency for the public to choose to save at Bank Syariah Indonesia. This study is expected to contribute to the development of Islamic banking marketing strategies and serve as a reference for future research.